1995
DOI: 10.1017/s1355617700000114
|View full text |Cite
|
Sign up to set email alerts
|

Ecological implications of limb apraxia: Evidence from mealtime behavior

Abstract: Humans learn skilled acts in order to effectively interact with their environment. A loss of the ability to perform skilled acts is termed apraxia. Apraxia has been thought to be of theoretical interest, but the ecological implications of apraxia are controversial and have not been fully studied. We examined ten patients with unilateral left hemisphere cerebral infarctions (eight of whom were apraxic) and compared their mealtime eating behavior to a group of neurologically normal, age-matched controls. The str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(71 citation statements)
references
References 8 publications
1
67
0
3
Order By: Relevance
“…Dyspraxia may adversely affect activities of daily living (Buzzelli et al, 1998). SpecificaUy, Foundas et al (1995) found that increased severity of dyspraxia of the limbs was related to an increased number of errors in mealtime eating behaviour and the sequencing of mealtime activities. Additionally, the presence of dyspraxia has also been found to predict subjective well-being one year after stioke (Wyller et al, 1997).…”
Section: Praxismentioning
confidence: 99%
See 1 more Smart Citation
“…Dyspraxia may adversely affect activities of daily living (Buzzelli et al, 1998). SpecificaUy, Foundas et al (1995) found that increased severity of dyspraxia of the limbs was related to an increased number of errors in mealtime eating behaviour and the sequencing of mealtime activities. Additionally, the presence of dyspraxia has also been found to predict subjective well-being one year after stioke (Wyller et al, 1997).…”
Section: Praxismentioning
confidence: 99%
“…Dyspraxia can have a significant effect on patient functional ability affecting eating behaviour (Foundas et al, 1995) and other activities of daily living. As a cause of functional limitations, dyspraxia may indirectly affect strain in caregivers, through limiting the abilities of the patient.…”
Section: Patient Characteristics and Cognitive Impairmentmentioning
confidence: 99%
“…The case of Mary demonstrates how an understanding of psychogenic causation (Pietrukowic and Johnson, 1991) was necessary to manage aggressive resistance, whilst for Jack an understanding of neurogenic causation, i.e. apraxia (Foundas et al, 1995;Tate and McDonald, 1995) was necessary to reduce the same set of behaviours. Eastley and Wilcock (1997) note that aggressive behaviour occurs in approximately one in five SDAT sufferers and is associated with male gender and dyspraxia.…”
Section: Discussionmentioning
confidence: 99%
“…Although some apraxic patients present right sided hemiplegia and their errors may be associated with the paralysis of the nondominant left hand, there is evidence of their pathological nature by observing the behaviour of healthy people when manipulating objects with the nondominant hand [10,11].…”
Section: Use Of Toolsmentioning
confidence: 99%